Degradation-controllable temporary plugging material as well as preparation method and application thereof
By coating hydrophobic materials on the surface of the temporary plugging material and dispersing the emulsifier to form a hydrophobic layer, the problem of the existing temporary plugging materials degradation in storage and transportation is solved, and precise degradation is achieved at different formation temperatures, improving the controllability and effect of the temporary plugging process.
Patent Information
- Application Number
- CN202311283325.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-07
AI Technical Summary
During storage and transportation, existing temporary plugging materials are easily degraded early by humid air, affecting the temporary plugging effect, and it is difficult to accurately control the degradation at different formation temperatures.
By coating a hydrophobic material (such as polyethylene wax) on the surface of the temporary blocking substrate and dispersing the emulsifier in the hydrophobic material, a hydrophobic layer is formed to inhibit moisture diffusion and control material degradation.
The degradation delay of temporary plugging materials is achieved without moisture during storage and transportation, and the material degradation is accurately controlled after reaching the target formation, improving the controllability and effect of the temporary plugging process.
Smart Images

Figure BDA0004479004150000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of temporary plugging materials, and in particular relates to a temporary plugging material with controllable degradation, and specifically relates to a temporary plugging material with controllable degradation, and a preparation method and application thereof. Background Art
[0002] Oil is an important component of the current industrial energy supply. A stable oil supply plays an important role in economic and social development. In the process of oil development, fracturing has become an important means of stratum transformation in order to increase oil and gas production.
[0003] By injecting a large amount of liquid into the formation under high pressure, a large number of cracks can be generated in the formation, increasing the production channels of oil and gas and improving the output. During fracturing, different formations will be fractured in stages, and bridge plugs are required to isolate the stages. Within the stage, temporary plugging balls or temporary plugging particles are also required between different cracked clusters to seal the first-open clusters, thereby forcing the liquid flow to turn to the second-open clusters, thereby improving the effect of fracturing transformation.
[0004] In the above process, temporary plugging materials are required for the separation between sections and the plugging of the priority opening clusters within the sections. Temporary plugging materials are a kind of material that can be degraded in the fracturing fluid. During the fracturing process, they can play a plugging role. After the fracturing is completed, they will degrade by themselves, will not affect the subsequent construction, and do not require special processing procedures. It can simplify the construction process, reduce the difficulty of construction, and improve the formation transformation effect.
[0005] All kinds of polyester products with ester groups in the main chain can be used as temporary plugging materials because they can be hydrolyzed in water and degraded to become ineffective. However, in order to ensure rapid degradation after underground construction is completed, materials that degrade quickly are generally selected. This also causes the material to begin to degrade during the storage period and the early stage of construction before it reaches the designated formation location and the construction is not completed, affecting the temporary plugging effect. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present invention provides a temporary plugging material with controllable degradation, and a preparation method and application thereof, wherein a hydrophobic material (such as polyethylene wax) is coated on the surface of a temporary plugging substrate to inhibit the diffusion of water into the interior of the temporary plugging substrate within a certain temperature range, thereby achieving the purpose of controllable degradation; at the same time, an emulsifier is dispersed in the hydrophobic material (such as polyethylene wax) to help achieve a degradation environment, thereby releasing the protection of the polyethylene wax and promoting the degradation of the material.
[0007] A first aspect of the present invention is to provide a temporary plugging material with controllable degradation, which comprises a temporary plugging matrix and a hydrophobic layer wrapped on the surface of the temporary plugging matrix.
[0008] In the temporary plugging material of the present invention, the temporary plugging matrix is selected from one or more of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, and polyhydroxyalkanoate.
[0009] In the temporary plugging material of the present invention, the hydrophobic layer is selected from a mixed material including a hydrophobic material and an emulsifier.
[0010] In the temporary plugging material of the present invention, based on 100wt% of the hydrophobic layer, the emulsifier is 0.1-10wt%, preferably 1-5wt%; and / or, based on 100wt% of the hydrophobic layer, the hydrophobic material is 90-99.9wt%, preferably 95-99wt%.
[0011] In the temporary plugging material of the present invention, the hydrophobic material is selected from at least one hydrophobic material with a melting point between 80 and 135°C; preferably, the hydrophobic material is selected from at least one hydrophobic material with a melting point 3 to 8°C lower than the target formation temperature; more preferably, the hydrophobic material is selected from polyethylene wax.
[0012] In the temporary plugging material of the present invention, the emulsifier is selected from at least one of nonionic surfactants; preferably, the emulsifier is selected from at least one of sorbitan laurate, tetraethylene glycol monolaurate, polyether sorbitan monostearate, hexaethylene glycol monostearate, polyether lanolin ether, polyether sorbitan monooleate, polyether sorbitan tristearate, polyether sorbitan trioleate, polyether sorbitan monolaurate, nonylphenol polyether, polyether oleyl ether, polyether methyl glucoside sesquioleate, and polyether sorbitan monopalmitate, and the polyether is preferably polyoxyethylene ether, polyoxypropylene ether, or polyoxyethylene-propylene copolymer.
[0013] In the temporary plugging material of the present invention, the emulsifier is selected from sorbitan laurate, tetraethylene glycol monolaurate, polyoxyethylene (4EO) sorbitan monostearate, hexaethylene glycol monostearate, polyoxypropylene (5PO) lanolin ether, polyoxyethylene (5EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan tristearate, polyoxyethylene (20EO) sorbitan trioleate, polyoxyethylene (4EO) sorbitan monolaurate, nonyl At least one of phenol polyoxyethylene (10) ether, polyoxyethylene (20EO) sorbitan monostearate, polyoxyethylene (20EO) oleyl alcohol ether, polyoxyethylene (20EO) methyl glucoside sesquioleate, polyoxyethylene (16EO) lanolin alcohol ether, polyoxyethylene (25EO) lanolin alcohol ether, polyoxyethylene (20EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan monopalmitate, and polyoxyethylene (20EO) sorbitan monolaurate.
[0014] The second aspect of the present invention is to provide a method for preparing a degradation-controllable temporary plugging material, which is preferably used to prepare the above-mentioned degradation-controllable temporary plugging material. The preparation method comprises: mixing the emulsifier with the hydrophobic material in a molten state to obtain a hydrophobic layer mixture, adding a temporary plugging matrix to the hydrophobic layer mixture, taking it out after immersion, and obtaining the degradation-controllable temporary plugging material after cooling.
[0015] In the preparation method of the present invention, the hydrophobic material is heated to at least 50° C. above its melting point to obtain the hydrophobic material in a molten state.
[0016] In the preparation method of the present invention, the emulsifier is evenly dispersed in the hydrophobic material in a molten state by a high-speed emulsifier to obtain the hydrophobic layer mixture.
[0017] In the preparation method of the present invention, a temporary plugging matrix is added to the hydrophobic layer mixture, immersed for more than 5 seconds and then taken out, and cooled after the surface liquid flows out, so as to obtain the temporary plugging material with controllable degradation.
[0018] The third aspect of the present invention is to provide the use of the temporary plugging material in fracturing. DETAILED DESCRIPTION
[0019] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0020] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0021] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0022] One of the purposes of the present invention is to provide a temporary plugging material with controllable degradation, which comprises a temporary plugging matrix and a hydrophobic layer wrapped on the surface of the temporary plugging matrix.
[0023] In a preferred embodiment, the temporary plugging matrix is selected from degradable materials.
[0024] The temporary plugging matrix can be selected from any material known in the art that can be used as a temporary plugging agent.
[0025] In a further preferred embodiment, the temporary plugging matrix is selected from one or more of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, and polyhydroxyalkanoate.
[0026] In a further preferred embodiment, the melting index of the temporary plugging matrix is above 1 g / 10 min.
[0027] In a preferred embodiment, the hydrophobic layer is selected from a mixed material including a hydrophobic material and an emulsifier.
[0028] Among them, wrapping a layer of the hydrophobic layer on the surface of the temporary plugging substrate can effectively prevent degradation caused by moisture such as humid air, extend the shelf life of the product, and also simplify the packaging of the product without the need for vacuum or moisture-proof packaging, thereby solving the problem that the existing temporary plugging materials begin to be degraded by the influence of humid air during the storage period after being manufactured.
[0029] The present invention can also solve the problem that the existing temporary plugging materials cannot be effectively degraded after entering the formation after being hydrophobically coated. As mentioned above, if the temporary plugging materials are simply wrapped with some hydrophobic materials, the problem of delayed degradation can be solved. However, since the degradation of degradable materials requires the participation of water, if the moisture is completely isolated so that the material cannot be brought into contact with water after construction, it cannot be effectively degraded. By compounding an emulsifier with an HLB value greater than 8 in the hydrophobic material (preferably polyethylene wax), the hydrophobic material (preferably polyethylene wax) can be dispersed by the emulsifier after melting at high temperature, thereby destroying the hydrophobic layer and allowing the material to degrade smoothly.
[0030] Specifically, taking polyethylene wax as an example, after entering the target formation, the polyethylene wax melts, is then emulsified and dispersed by the emulsifier, and is peeled off from the biodegradable material matrix. After separation from the polyethylene wax, the degradation of the biodegradable material will not be affected, and the polyethylene wax will not degrade, but after the polyethylene wax is dispersed in water by the emulsifier, it will be discharged.
[0031] In a further preferred embodiment, based on 100 wt % of the hydrophobic layer, the emulsifier is 0.1 to 10 wt %, preferably 1 to 5 wt %; and the hydrophobic material is 90 to 99.9 wt %, preferably 95 to 99 wt %.
[0032] For example, based on 100wt% of the hydrophobic layer, the emulsifier is 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%; the hydrophobic material is 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt%, 99.5wt% or 99.9wt%.
[0033] In a further preferred embodiment, the average thickness of the hydrophobic layer is 10-500 μm, for example, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm.
[0034] In a preferred embodiment, the hydrophobic material is selected from at least one hydrophobic material having a melting point between 80 and 135°C (eg, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 135°C).
[0035] In a further preferred embodiment, the hydrophobic material is selected from at least one hydrophobic material having a melting point 3 to 8°C (eg, 3°C, 4°C, 5°C, 6°C, 7°C or 8°C) lower than the target formation temperature.
[0036] Among them, the technical problem to be solved by the present invention is to solve the problem that the existing temporary plugging materials have low adaptability to different degradation temperatures of the formation. The present invention uses hydrophobic materials (such as polyethylene wax) with different melting points, so that the material can only effectively start to degrade after reaching the target formation and being in a specific temperature environment.
[0037] In a further preferred embodiment, the hydrophobic material is selected from polyethylene wax; preferably, the melting point of the polyethylene wax is 80-135°C, and more preferably, the melting point of the polyethylene wax is 3-8°C lower than the target formation temperature.
[0038] For example, the melting point of the polyethylene wax is 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 135°C. More preferably, the melting point of the polyethylene wax is 3°C, 4°C, 5°C, 6°C, 7°C or 8°C lower than the temperature of the target formation.
[0039] In a preferred embodiment, the emulsifier is selected from at least one of nonionic surfactants; preferably, the emulsifier is selected from at least one of sorbitan laurate, tetraethylene glycol monolaurate, polyether sorbitan monostearate, hexaethylene glycol monostearate, polyether lanolin ether, polyether sorbitan monooleate, polyether sorbitan tristearate, polyether sorbitan trioleate, polyether sorbitan monolaurate, nonylphenol polyether, polyether oleyl ether, polyether methyl glucoside sesquioleate, and polyether sorbitan monopalmitate, and the polyether is preferably polyoxyethylene ether, polyoxypropylene ether, or polyoxyethylene-propylene copolyether.
[0040] In a further preferred embodiment, the emulsifier is selected from sorbitan laurate, tetraethylene glycol monolaurate, polyoxyethylene (4EO) sorbitan monostearate, hexaethylene glycol monostearate, polyoxypropylene (5PO) lanolin ether, polyoxyethylene (5EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan tristearate, polyoxyethylene (20EO) sorbitan trioleate, polyoxyethylene (4EO) sorbitan monolaurate, nonyl At least one of phenol polyoxyethylene (10) ether, polyoxyethylene (20EO) sorbitan monostearate, polyoxyethylene (20EO) oleyl alcohol ether, polyoxyethylene (20EO) methyl glucoside sesquioleate, polyoxyethylene (16EO) lanolin alcohol ether, polyoxyethylene (25EO) lanolin alcohol ether, polyoxyethylene (20EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan monopalmitate, and polyoxyethylene (20EO) sorbitan monolaurate.
[0041] In a further preferred embodiment, the HLB value of the emulsifier is greater than 8.
[0042] In a further preferred embodiment, the emulsifier is in a dispersed state in the hydrophobic material (preferably polyethylene wax) and can be well dispersed.
[0043] The present invention mainly solves the problem that ordinary temporary plugging materials will be affected by water and degrade in advance and lose mechanical properties before reaching the target formation during transportation, storage and application, and also improves the response accuracy of the degradation characteristics of the material at different temperatures. By adding emulsifiers to hydrophobic materials (such as polyethylene wax) with different melting points, and attaching them to the temporary plugging substrate or the surface of the workpiece, a hydrophobic protective film is formed to inhibit moisture from entering the interior of the material, thereby eliminating the need for moisture-proof packaging during storage and transportation. During construction, degradation can also be started more accurately at different formation temperatures, thereby improving the controllability of the temporary plugging process.
[0044] The second object of the present invention is to provide a method for preparing a degradation-controllable temporary plugging material, which is preferably used to prepare the degradation-controllable temporary plugging material described in one of the objects of the present invention. The preparation method comprises: mixing the emulsifier with the hydrophobic material in a molten state to obtain a hydrophobic layer mixture, adding a temporary plugging matrix to the hydrophobic layer mixture, taking it out after immersion, and obtaining the degradation-controllable temporary plugging material after cooling.
[0045] In a preferred embodiment, the hydrophobic material is heated to at least 50° C. above its melting point to obtain the hydrophobic material in a molten state.
[0046] In a preferred embodiment, the hydrophobic layer mixture is obtained by uniformly dispersing an emulsifier in the molten hydrophobic material using a high-speed emulsifier.
[0047] In a preferred embodiment, a temporary plugging matrix is added to the hydrophobic layer mixture, immersed for more than 5 seconds and then taken out, and cooled after the surface liquid flows out, to obtain the temporary plugging material with controllable degradation.
[0048] In a preferred embodiment, the temporary plugging matrix is spherical, granular or any other shape, such as a temporary plugging ball, temporary plugging granules or other shaped parts.
[0049] The target product of the temporary plugging matrix is made by extrusion, injection molding, machining and other processes. For example, the temporary plugging ball is obtained by injection molding, the temporary plugging granules are obtained by extrusion granulation, and other products such as bridge plugs are obtained by machining extruded rods.
[0050] In the method described in the present invention: (1) the degradable matrix is made into a target product by extrusion, injection molding, machining and other processes; for example, temporary plugging balls are obtained by injection molding, temporary plugging particles are obtained by extrusion granulation, and other products such as bridge plugs are obtained by machining extruded rods; (2) the hydrophobic material (such as polyethylene wax) is heated to a temperature above 50°C above the melting point, an emulsifier is added to the hydrophobic material (such as polyethylene wax), and the emulsifier is evenly dispersed in the hydrophobic material (such as polyethylene wax) by a high-speed emulsifier at high temperature; (3) the target product of the temporary plugging matrix is immersed in the above-mentioned dispersion, taken out after more than 5 seconds, the surface hydrophobic material (such as polyethylene wax) liquid is drained, and cooled to obtain the finished product.
[0051] The temporary plugging material obtained by the technical solution of the present invention is coated with a hydrophobic material (such as polyethylene wax) on the surface, which can isolate moisture from the temporary plugging material during storage and the initial stage of construction. No moisture-proof or vacuum storage is required during the storage period. In the initial stage of construction, before reaching the designated stratum, the temporary plugging material will not come into contact with water and begin to degrade.
[0052] The temporary plugging material obtained by the technical solution of the present invention has a hydrophobic material (such as polyethylene wax) coated on the surface with different melting points, which can be selected according to the temperature of the target formation, so that the temporary plugging material will not begin to degrade until it reaches the target formation and is in a specific temperature environment.
[0053] The temporary plugging material obtained by the technical solution of the present invention has a hydrophobic material (such as polyethylene wax) coated on the surface, which contains an emulsifier with an HLB value greater than 8. When the material is in water with a temperature greater than the melting point of the hydrophobic material (such as polyethylene wax), the emulsifier will assist the dispersion of the hydrophobic material (such as polyethylene wax) in the water, thereby ensuring the contact between water and the temporary plugging material, so that the material will not be degraded due to the coating of the hydrophobic layer.
[0054] Compared with the untreated temporary plugging material, the temporary plugging material obtained by the technical solution of the present invention has a strength retention rate of more than 98% after three months when placed open without sealing or vacuum packaging. The temporary plugging material obtained by the present invention can be effectively degraded in water at a specific temperature (such as the temperature of the target formation). The temporary plugging material obtained by the present invention will degrade normally in water whose ambient temperature reaches the specific temperature, and will not lose its degradation characteristics due to the influence of the technical solution.
[0055] The third object of the present invention is to provide the temporary plugging material described in the first object of the present invention or the temporary plugging material obtained by the preparation method described in the second object of the present invention for use in fracturing.
[0056] The "at least one" or "multiple" described in the present invention includes one, two or more, three or more, four or more. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article. In the following, in principle, the various technical solutions can be combined with each other to obtain new technical solutions, which should also be regarded as specifically disclosed in this article.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The surface of the temporary plugging material of the present invention is coated with a hydrophobic material (such as polyethylene wax), which can isolate moisture from the temporary plugging matrix during storage and the initial construction period, and does not require moisture-proof or vacuum storage during storage;
[0059] (2) The temporary plugging material of the present invention will not degrade before reaching the target formation. When reaching the target formation, the emulsifier will assist the dispersion of the hydrophobic material (such as polyethylene wax) in water, thereby ensuring the contact between water and the temporary plugging matrix, and the temporary plugging matrix will be degraded.
[0060] [Example and Comparative Example]
[0061] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0062] [Example 1]
[0063] A polyglycolide temporary plugging ball with a diameter of 15 mm was obtained;
[0064] A polyethylene wax having a melting point of 120° C. is heated to a temperature 50° C. above the melting point, an emulsifier, sorbitan laurate, is added to the polyethylene wax, the amount of the emulsifier being 1.5wt% based on the total weight of the emulsifier and the polyethylene wax being 100wt%, and the emulsifier is uniformly dispersed in the polyethylene wax by a high-speed emulsifier at the system temperature to obtain a dispersion;
[0065] The polyglycolide temporary plugging ball is immersed in the above dispersion, taken out after more than 5 seconds, the polyethylene wax liquid on the surface is drained, and cooled to obtain a finished product. The average thickness of the hydrophobic layer is 100 μm.
[0066] [Example 2]
[0067] A polylactide temporary plugging ball with a diameter of 10 mm was obtained;
[0068] A polyethylene wax having a melting point of 95° C. is heated to a temperature 50° C. above the melting point, an emulsifier polyoxyethylene (20EO) sorbitan monostearate is added to the polyethylene wax, the amount of the emulsifier being 3wt% based on the total weight of the emulsifier and the polyethylene wax being 100wt%, and the emulsifier is uniformly dispersed in the polyethylene wax by a high-speed emulsifier at the system temperature to obtain a dispersion;
[0069] The polylactide temporary plugging ball is immersed in the above dispersion, taken out after more than 5 seconds, the polyethylene wax liquid on the surface is drained, and cooled to obtain a finished product. The average thickness of the hydrophobic layer is 100 μm.
[0070] [Example 3]
[0071] Obtaining polyglycolide temporary plugging particles with a particle size of 100 μm-200 μm;
[0072] A polyethylene wax having a melting point of 110° C. is heated to a temperature 50° C. above the melting point, an emulsifier polyoxyethylene (20EO) sorbitan monopalmitate is added to the polyethylene wax, the amount of the emulsifier being 4.5wt% based on the total weight of the emulsifier and the polyethylene wax being 100wt%, and the emulsifier is uniformly dispersed in the polyethylene wax by a high-speed emulsifier at the system temperature to obtain a dispersion;
[0073] The polyglycolide temporary plugging particles are immersed in the above dispersion, taken out after more than 5 seconds, the polyethylene wax liquid on the surface is drained, and the finished product is obtained by cooling. The average thickness of the hydrophobic layer is 100 μm.
[0074] [Example 4]
[0075] A polylactide temporary plugging ball with a diameter of 45 mm was obtained;
[0076] A polyethylene wax having a melting point of 100° C. is heated to a temperature 50° C. above the melting point, an emulsifier nonylphenol polyoxyethylene (10) ether is added to the polyethylene wax, the amount of the emulsifier being 5wt% based on the total weight of the emulsifier and the polyethylene wax being 100wt%, and the emulsifier is uniformly dispersed in the polyethylene wax by a high-speed emulsifier at the system temperature to obtain a dispersion;
[0077] The polylactide temporary plugging ball is immersed in the above dispersion, taken out after more than 5 seconds, the polyethylene wax liquid on the surface is drained, and cooled to obtain a finished product. The average thickness of the hydrophobic layer is 100 μm.
[0078] [Comparative Example 1]
[0079] A polyglycolide temporary plugging ball with a diameter of 15 mm is obtained, and polyethylene wax with a melting point of 120°C is heated to 50°C above the melting point to obtain polyethylene wax liquid, and the polyglycolide temporary plugging ball is immersed in the above polyethylene wax liquid, taken out after more than 5 seconds, the polyethylene wax liquid on the surface is drained, and cooled to obtain a finished product.
[0080] [Comparative Example 2]
[0081] A polylactide temporary plugging ball with a diameter of 10 mm was obtained.
[0082] [Comparative Example 3]
[0083] Obtaining polyglycolide temporary plugging particles with a diameter of 100 μm-200 μm;
[0084] Polyoxyethylene (20EO) sorbitan monopalmitate is melted to form a molten liquid (this emulsifier is solid at room temperature and can be impregnated after melting). The polyglycolide temporary plugging particles are immersed in the molten liquid for more than 5 seconds, then taken out, the surface liquid is drained and cooled to obtain a finished product.
[0085] [Experimental Example 1]
[0086] The samples obtained in the embodiment and the comparative example were placed open at room temperature without moisture-proof and vacuum packaging. After three months, the strength retention rate was tested on a universal testing machine, as shown in Table 1.
[0087] Table 1 Long-term storage characteristics of temporary plugging material products of the embodiments and comparative examples
[0088] Strength retention rate % Example 1 98.3 Example 2 99.1 Example 3 98.5 Example 4 98.1 Comparative Example 1 98 Comparative Example 2 78.5 Comparative Example 3 38.3
[0089] It can be seen that, due to the protection of the polyethylene wax layer, the strength retention rates of Examples 1-4 and Comparative Example 1 are relatively high when placed in the open for a long time without being affected by humid air, while the strength of Comparative Examples 2 and 3 without polyethylene wax protection is significantly reduced. The above data can prove that the product obtained by the technical solution can simplify the storage and transportation methods and ensure stable performance during the storage period.
[0090] [Experimental Example 2]
[0091] Since the temporary plugging material must be degraded under specific conditions (referring to the target formation) in its final application state, the temporary plugging material is kept warm in water for 24 hours at a temperature 5°C lower and higher than the corresponding polyethylene wax melting point. When the temperature is higher than 98°C, the test is carried out in a high-pressure sealed container, and when the temperature is lower than 98°C, the test is carried out in a normal-pressure blue-capped reagent bottle.
[0092] The strength retention rates of the products were tested on a universal testing machine. The data are shown in Table 2.
[0093] Table 2 High temperature degradation characteristics of the embodiments and comparative examples
[0094]
[0095] It can be seen that the product obtained in the embodiment of the present invention can effectively maintain a high strength retention rate when the temperature is 5°C lower than the melting point of the polyethylene wax, proving that the polyethylene wax can effectively protect the temporary plugging matrix, isolate it from contact with water, and basically will not be degraded. When the temperature is 5°C higher than the melting point of the polyethylene wax, the polyethylene wax melts, and the emulsifier helps the polyethylene wax to disperse in the water, removes the isolation of the temporary plugging matrix from water, and allows the temporary plugging matrix to fully degrade.
[0096] Relatively speaking: In the sample of Comparative Example 1, since there is no emulsifier in the polyethylene wax, although the polyethylene wax becomes a melt after 5°C above the melting point, it is still adsorbed on the surface of the temporary plugging material, isolating moisture, so that the material cannot be fully degraded. In Comparative Example 2, since there is no protection of polyethylene wax, it degrades faster at both temperatures. In Comparative Example 3, although there is an emulsifier, there is no polyethylene wax, and moisture cannot be effectively isolated, so it still degrades faster.
[0097] The above data can prove that the product obtained by the present invention will only begin to degrade in water at a specific temperature, and after the temperature reaches the specified temperature, the polyethylene wax layer will be dispersed and discharged with the formation water, and the remaining will be dissolved and discharged when encountering crude oil. It will not affect the subsequent degradation characteristics. Products that have not been processed by this technical solution do not have this temperature response characteristic. Whether in long-term storage or when the temporary plugging material has not reached the temperature environment of the specified formation, it will begin to degrade, which is not conducive to the product playing a role in the target position. The above also confirms the superiority of the present invention.
[0098] Note: Since both Example 3 and Comparative Example 3 are in the form of fine powder, the strength cannot be directly measured. Therefore, in actual measurement, the powders before and after aging are melt-molded into 15 mm spheres and tested in the same way as Example 1.
[0099] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A degradation-controlled temporary plugging material, comprising a temporary plugging matrix and a hydrophobic layer wrapped on the surface of the temporary plugging matrix.
2. The temporary plugging material according to claim 1, characterized in that: The temporary plugging matrix is selected from one or more of polyglycolide, polylactide, polybutylene succinate, polycaprolactone, polybutylene terephthalate-adipate, polybutylene terephthalate, polybutylene succinate adipate, polymethyl ethylene carbonate, and polyhydroxyalkanoate.
3. The temporary plugging material according to claim 1 or 2, characterized in that: The hydrophobic layer is selected from a mixed material including a hydrophobic material and an emulsifier.
4. The temporary plugging material according to claim 3, characterized in that: Based on 100wt% of the hydrophobic layer, the emulsifier is 0.1-10wt%, preferably 1-5wt%; and / or, based on 100wt% of the hydrophobic layer, the hydrophobic material is 90-99.9wt%, preferably 95-99wt%.
5. The temporary plugging material according to claim 3, characterized in that: The hydrophobic material is selected from at least one of the hydrophobic materials with a melting point between 80 and 135° C.; preferably, the hydrophobic material is selected from at least one of the hydrophobic materials with a melting point 3 to 8° C. lower than the target formation temperature.
6. The temporary plugging material according to claim 3, characterized in that: The emulsifier is selected from at least one of nonionic surfactants; preferably, the emulsifier is selected from at least one of sorbitan laurate, tetraethylene glycol monolaurate, polyether sorbitan monostearate, hexaethylene glycol monostearate, polyether lanolin ether, polyether sorbitan monooleate, polyether sorbitan tristearate, polyether sorbitan trioleate, polyether sorbitan monolaurate, nonylphenol polyether, polyether oleyl ether, polyether methyl glucoside sesquioleate, and polyether sorbitan monopalmitate, and the polyether is preferably polyoxyethylene ether, polyoxypropylene ether, or polyoxyethylene-propylene copolymer.
7. The temporary plugging material according to claim 6, characterized in that: The emulsifier is selected from the group consisting of sorbitan laurate, tetraethylene glycol monolaurate, polyoxyethylene (4EO) sorbitan monostearate, hexaethylene glycol monostearate, polyoxypropylene (5PO) lanolin ether, polyoxyethylene (5EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan tristearate, polyoxyethylene (20EO) sorbitan trioleate, polyoxyethylene (4EO) sorbitan monolaurate, nonylphenol polyoxyethylene ( 10) at least one of ether, polyoxyethylene (20EO) sorbitan monostearate, polyoxyethylene (20EO) oleyl ether, polyoxyethylene (20EO) methyl glucoside sesquioleate, polyoxyethylene (16EO) lanolin alcohol ether, polyoxyethylene (25EO) lanolin alcohol ether, polyoxyethylene (20EO) sorbitan monooleate, polyoxyethylene (20EO) sorbitan monopalmitate and polyoxyethylene (20EO) sorbitan monolaurate.
8. A method for preparing a controllable degradation temporary plugging material, preferably used for preparing the controllable degradation temporary plugging material according to any one of claims 1 to 7, the method comprising: The emulsifier is mixed with the hydrophobic material in a molten state to obtain a hydrophobic layer mixture, a temporary plugging matrix is added to the hydrophobic layer mixture, taken out after immersion, and the degradation-controllable temporary plugging material is obtained after cooling.
9. The preparation method according to claim 8, characterized in that: The hydrophobic material is heated to at least 50° C. above its melting point to obtain the hydrophobic material in a molten state.
10. The preparation method according to claim 8, characterized in that: The hydrophobic layer mixture is obtained by uniformly dispersing the emulsifier in the molten hydrophobic material using a high-speed emulsifier.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The temporary plugging matrix is added into the hydrophobic layer mixture, and taken out after being immersed for more than 5 seconds, and cooled after the surface liquid flows out, so as to obtain the temporary plugging material with controllable degradation.
12. Use of the temporary plugging material according to any one of claims 1 to 7 or the temporary plugging material obtained by the preparation method according to any one of claims 8 to 11 in fracturing.
Citation Information
Patent Citations
High-strength degradable temporary plugging spheres for oil and gas well as well as preparation method and application of temporary plugging spheres
CN108587587A
Degradable material for temporary plugging and fracturing and preparation method thereof
CN111334013A
Self-cleaning degradable fracturing temporary plugging agent as well as preparation method and application thereof
CN111621272A
Temporary plugging ball for fracturing as well as preparation method and application of temporary plugging ball
CN114958321A
Double-response self-degradable temporary plugging agent and preparation method thereof
US20210380865A1